Marketing management : text and cases, 2nd year , 3rd semester BMS - Kale N.G. and Mehta Ahmed (Vipul Prakashan, Mumbai, 2003)
B.M.S.
ENGLISH
Keywords: Marketing management : text and cases, 2nd year , 3rd semester BMS; B.M.S.; B.M.S.